Thermodynamic Study on the Sn Removal from Molten Steel by CaO-SiO2-Al2O3 Slag - Y.-H. Hai; X. Zhang; G.-J. Ma; D.-L. Zheng; J. Xu; M.-K. Liu (Archives of Metallurgy and Materials)
The utilization of raw materials such as steel scrap in the steelmaking process might introduce the impurity element Sn, which significantly deteriorates the steel’s performance. Therefore, it is necessary to fully understand the mechanism of removing the residual element Sn from the molten steel. This study performed a thermodynamic calculation and investigation of residual element Sn removal in molten steel using the CaO-SiO2-Al2O3 slag. The results show that when the dissolved O content in the molten steel is greater than 0.0005% and the Sn content is less than 0.254%, it is difficult to remove Sn from the molten steel using the CaO-SiO2-Al2O3 slag alone, without incorporating other Sn removal methods. Molten slag can only help remove Sn from molten steel by adsorbing the Sn removal products. When the contents of CaO, SiO2, and Al2O3 are 20~40 wt.%, increasing the SiO2 content of the CaO-SiO2-Al2O3 slag enhances the slag’s ability to absorb Sn removal products. However, as the content of Al2O3 or CaO in the slag increases, the slag’s Sn capacity decreases dramatically. When the CaO/Al2O3 ratio in the slag is 1 and the SiO2 content is 40%, the Sn capacity reaches a maximum of 2.13×10–7. When the CaO/SiO2 ratio in the slag is 1 and the Al2O3 content is 20%, the Sn capacity reaches a maximum of 1.43×10–7. Meanwhile, when the SiO2/Al2O3 ratio in the slag is 1 and the CaO content is 20%, the Sn capacity reaches its maximum of 4.15×10–7.